1977
DOI: 10.1126/science.302032
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Suppressor T Cells in Systemic Lupus Erythematosus by Thymosin and Cultured Thymic Epithelium

Abstract: Patients with systemic lupus erythematosus lacked suppressor T cell function. Suppressor cell activity was induced in cells from many of these patients by incubation with thymosin or cultured thymic epithelium. These results suggest that thymic manipulation may be a useful therapeutic modality in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
1
3

Year Published

1978
1978
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(61 citation statements)
references
References 16 publications
5
52
1
3
Order By: Relevance
“…Thus, the finding of a non-T cell abnormality in the autologous MLR in active but not in inactive SLE patients is consistent with the previous functional studies. T cell defects observed in patients with SLE include impaired delayed hypersensitivity (17,18), reduced responsiveness to stimulation with allogeneic cells and T cell mitogens (19,20), and impaired generation of suppressor T cells (21)(22)(23)(24). SLE patients with active disease are especially predisposed to all of the abnormalities; however, defects in suppressor cell generation have been observed even in patients in remission (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the finding of a non-T cell abnormality in the autologous MLR in active but not in inactive SLE patients is consistent with the previous functional studies. T cell defects observed in patients with SLE include impaired delayed hypersensitivity (17,18), reduced responsiveness to stimulation with allogeneic cells and T cell mitogens (19,20), and impaired generation of suppressor T cells (21)(22)(23)(24). SLE patients with active disease are especially predisposed to all of the abnormalities; however, defects in suppressor cell generation have been observed even in patients in remission (23).…”
Section: Discussionmentioning
confidence: 99%
“…T cell defects observed in patients with SLE include impaired delayed hypersensitivity (17,18), reduced responsiveness to stimulation with allogeneic cells and T cell mitogens (19,20), and impaired generation of suppressor T cells (21)(22)(23)(24). SLE patients with active disease are especially predisposed to all of the abnormalities; however, defects in suppressor cell generation have been observed even in patients in remission (23). These findings are consistent with the present studies of the autologous MLR patients with active SLE are defective with regard to all T cell subpopulations studied, whereas those with inactive SLE are abnormal only with respect to Ty cells.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies demonstrated that patients with active SLE had a loss of suppressor T lymphocyte function (22)(23)(24)(25)(26)(27)(28). Several studies have emphasized the importance of anti-T cell antibodies in altering T cell number and function in patients with active SLE (7,8,(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…The suppression was no different from that (23,24) as well as T-cell subsets determined by a number of other methodologies (25)(26)(27)(28)(29). This is of particular relevance in light of the fact that in several in vitro systems, SLE has been demonstrated to manifest a deficiency of suppressor cell function (23,(30)(31)(32)(33)(34)(35). Although the actual suppressor cell in most of these systems has not been conclusively identified, at least in some systems of in vitro B-cell function, the TG cell has been demonstrated to be the suppressor cell (16).…”
Section: Resultsmentioning
confidence: 82%